The Impacts of Knowledge, Attitudes, and Actions on the Implementation of Biosecurity in the Management of Foot and Mouth Disease in Kuta Baro Subdistrict, Aceh Besar Regency - Rasyid, Baharun; Karunia, Nia; Notodiputro, Khairil Anwar; Indahwati, Indahwati; Mualifah, Laily Nissa Atul; Hasanah, Lailatul (Jurnal Peternakan, 2025)
.  Foot and Mouth Disease (FMD) is an animal disease caused by a virus from the Picornaviridae family with the genus Aphthovirus. This study aimed to assess the extent of knowledge, attitudes, and actions of cattle farmers in Kuta Baro Subdistrict, Aceh Besar District, in implementing biosecurity on their farms to prevent FMD. The sample used was 45 cattle farmers in four villages in Kuta Baro Subdistrict, Aceh Besar District, namely Cut Preh, Cut Beut, Lam Seunong, and Ujong Blang. This study used a questionnaire instrument and the data were analyzed using binary logistic regression analysis. The statistics exhibited that the percentages of farmers with poor knowledge, attitude, and action were 71.1%, 66.7%, and 68.9%, respectively. Furthermore, the results of the analysis revealed that there was a significant relationship between the attitudes and actions of farmers towards the infection of FMD virus in livestock. Meanwhile, the farmer’s knowledge did not have a significant role in handling FMD. The odds ratio showed that the odds of FMD cases decrease 0.593 times if there is an increase in farmers' attitudes towards biosecurity, and the odds of FMD cases decrease 0.666 times if there is an increase in farmers' actions towards biosecurity. The accuracy of this model reached 68.9%. Enhancements in farmers’ knowledge, attitudes, and actions towards implementing biosecurity have the potential to reduce the incidence of Foot and Mouth Disease (FMD) in livestock.